The demographic contributions of connectivity versus local dynamics to population growth of an endangered bird. Issue 3 (15th January 2021) - Reichert, Brian E.; Fletcher, Robert J.; Kitchens, Wiley M.
Abstract: Conservation and management increasingly focus on connectivity, because connectivity driven by variation in immigration rates across landscapes is thought to be crucial for maintaining local population and metapopulation persistence. Yet, efforts to quantify the relative role of immigration on population growth across the entire range of species and over time have been lacking. We assessed whether immigration limited local and range‐wide population growth of the endangered snail kite Rostrhamus sociabilis in Florida, USA, over 18 years using multi‐state, reverse‐time modelling that accounts for imperfect detection of individuals and unobservable states. Demographic contributions of immigration varied depending on the dynamics and geographic position of the local populations, were scale‐dependent and changed over time. By comparing the relative contributions of immigration versus local demography for periods of significant change in local abundance, we found empirical evidence for a disproportionately large role of immigration in facilitating population growth of a centrally located population—a connectivity 'hub'. The importance of connectivity changed depending of the spatial scale considered, such that immigration was a more important driver of population growth at small versus large spatial scales. Furthermore, the contribution of immigration was much greater during time periods when local population size was small, emphasizing abundance‐dependent rescue effects. Our findings suggest that efforts aimed at improving local breeding habitat will likely be most effective at increasing snail kite population growth. More broadly, our results provide much needed information on the role of connectivity for population growth, suggesting that connectivity conservation may have the greatest benefits when efforts focus on centrally located habitat patches and small populations. Furthermore, our results highlight that connectivity is highly dynamic over time and that interpreting the effects of connectivity at local scales may not transfer to region‐wide dynamics. Abstract : The authors work highlights the dynamic nature of the role of connectivity for population persistence. Effective conservation can be informed by identifying demographic rates most important for population growth. Their results indicate that that the level of importance can change considerably over time and space. Demographic contributions of connectivity to population growth were also scale dependent, suggesting that future assessments of the relative importance of connectivity on population viability should go beyond the local scale and that local resource management can have impacts on population dynamics in distant populations via dispersal linkages. Photo credit: A. Gonzalez, March 2020.